Chile y el medio ambiente : notas en los ámbitos interno e internacional - Lucas Garín, Andrea (Estudios Internacionales, 2005)
Since the beginning of 1990, Chile has deepened economic reforms in the field of free trade, in three main ways: multilateral, regional and bilateral. The article begins with an analysis of the internal environment regarding the institutional and legislative environmental policies applied in Chile and their projections, to address the regional perspective, represented by Mercosur and FTAA; and then review the bilateral agreements signed by Chile with more relevant environmental components, that is, the Chile-European Union Association Agreement and two Free Trade Agreements: Chile-Canada and Chile-United States. The conclusions highlight that a greater awareness of environmental protection will lead to a more serious position by Chile at the external and internal level.